2022
DOI: 10.1093/geroni/igab052
|View full text |Cite
|
Sign up to set email alerts
|

Peritraumatic Stress From a Disaster Increases Risk for Onset of Chronic Diseases Among Older Adults

Abstract: Background and Objectives Our understanding of the impact of disaster exposure on the physical health of older adults is largely based on hospital admissions for acute illnesses in the weeks following a disaster. Studies of longer-term outcomes have centered primarily on mental health. Missing have been studies examining whether exposure to disaster increases the risk for the onset of chronic diseases. We examined the extent to which 2 indicators of disaster exposure (geographic exposure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Specific CVD morbidity risks associated with cyclone exposures were estimated in four studies. 15 , 62 , 66 , 68 In the month following a large-scale hurricane (e.g., Hurricane Sandy), increased hospitalization risks were found for myocardial infarction [ (95% CI: 1.16, 1.28)] and stroke [ (95% CI: 1.03, 1.11)] for the general population 62 and for congestive heart failure for the people years of age [ (95% CI: 1.17, 1.21)]. 66 One cohort study on 909 individuals years of age reported no statistically significant higher risk of new-onset heart diseases for the participants who lived in high-impacted areas (census blocks with a storm surge of foot, of houses damaged or reported greater than the average number of housing assistance registrations) compared with those who did not in the 4 y after Hurricane Sandy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific CVD morbidity risks associated with cyclone exposures were estimated in four studies. 15 , 62 , 66 , 68 In the month following a large-scale hurricane (e.g., Hurricane Sandy), increased hospitalization risks were found for myocardial infarction [ (95% CI: 1.16, 1.28)] and stroke [ (95% CI: 1.03, 1.11)] for the general population 62 and for congestive heart failure for the people years of age [ (95% CI: 1.17, 1.21)]. 66 One cohort study on 909 individuals years of age reported no statistically significant higher risk of new-onset heart diseases for the participants who lived in high-impacted areas (census blocks with a storm surge of foot, of houses damaged or reported greater than the average number of housing assistance registrations) compared with those who did not in the 4 y after Hurricane Sandy.…”
Section: Resultsmentioning
confidence: 99%
“… 66 One cohort study on 909 individuals years of age reported no statistically significant higher risk of new-onset heart diseases for the participants who lived in high-impacted areas (census blocks with a storm surge of foot, of houses damaged or reported greater than the average number of housing assistance registrations) compared with those who did not in the 4 y after Hurricane Sandy. 68 Another case-crossover study on 74 tropical cyclones across 175 U.S. counties observed increased risks for being hospitalized owing to heart failure [ (95% CI: 1.04, 1.11)] but not for myocardial infarction, ischemic heart disease, cerebrovascular disease, heart rhythm disturbance, or peripheral vascular disease among the population years of age over the 10-d post-cyclone period. 15 These studies of CVD-related excess morbidity were not included in the meta-analysis because there were fewer than three comparable effect estimates for each specific outcome.…”
Section: Resultsmentioning
confidence: 99%
“…From a gerontological perspective, it is notable that natural disasters erupt frequently in current times ( Curran, 2013 ) and increasingly affect older populations ( Li et al, 2019 ). Older adults are vulnerable to disasters ( Sands et al, 2022 ; Tome et al, 2022 ). When disasters strike, it is difficult for some older adults to pay attention to and comprehend warning messages due to their sensory impairments in visual and hearing capacities ( Mayhorn, 2005 ).…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Additionally, numerous disaster-related stressors have been proven to be linked with disorders of metabolic functions, organ aging, parasecretion, as well as the disruption of healthy lifestyle behaviors ( Fukuda et al, 1999 ; Kivimaki et al, 2022 ; Razzoli et al, 2018 ). Hence, research on the impact of disasters specific to older adults is of rising importance ( Hikichi et al, 2020 ; Sands et al, 2022 ). Along this line of research, previous studies have demonstrated that disaster exposure is strongly associated with postdisaster health problems such as cardiometabolic risks, arthritis, diabetes, dementia, and depression among older adults ( Ikeda et al, 2020 ; Lee et al, 2016 ; Sharma et al, 2008 ; Shiba et al, 2019 ).…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Third, one risk factor is usually related to more than one NCD (stress, 91 unhealthy and/or hypercaloric diet, 8 , 9 , 53 obesity, 8 , 10 , 40 , 92 tobacco, 8 , 31 , 53 alcohol consumption, 93 environmental pollutants, 10 , 28 , 94 radiation, 95 and sedentary lifestyle 8 , 9 ). Likewise, an NCD is usually related to more than one risk factor 8 (cancer, 8 , 31 , 92 , 93 , 96 cardiovascular diseases, 8 , 29 , 31 , 93 chronic pulmonary diseases, 9 , 31 , 92 , 96 neurological disorders, 93 , 97 T2DM, 8 , 53 , 92 , 96 arthritis, 92 , 98 and premature senescence, 9 among others).…”
Section: The Epidemiologic Perspectivementioning
confidence: 99%